Fashion, performance, and performativity the complex spaces of fashion - Kollnitz, Andrea 1970-; Pecorari, Marco (Bloomsbury Visual Arts, 2022)
In the first comprehensive study of the interactions between fashion, performance and performativity, a group of international experts explore fashion as the ideal 'complex space' -- or, in other words, the ideal space where performance and performativity come together, according to the works of seminal theorists Eve Kosofsky Sedgwick and Andrew Parker. Bringing together Western and non-Western, historical and contemporary case studies and theories, the book explores the magazines, photography, exhibitions, global colonial divides, digital media, and more, which have become key markers of the fashion industry as we know it today. Using existing literature as a springboard and incorporating perspectives from fashion studies, art history, media studies and gender studies, as well as from artists and practitioners, Fashion, Performance, and Performativity is an innovative and essential work for students, scholars and practitioners across multiple disciplines.
Keywords: Performance -- Künste; Modefotografie; Mode; Ästhetik; Geschlechterforschung; Gesellschaft; Feminismus; Medienkunst; Konferenzschrift -- 2017 -- Loughborough